Status Pemanfaatan Perikanan Tuna Madidihang (Thunnus albacares) Berdasarkan Model Biologi Schaefer - Abgusta Fajri Wiranata; Budy - Wiryawan; Sugeng Hari Wisudo; Nimmi - Zulbainarni (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2018)
There are two types of population growth functionÂ  of the basic formulation of Schaeferâ€™s biology model, however in this study there is a difference in form and value of â€œrâ€ as one of a biology parameter.Â Â  In additionÂ  to the difference in the method by calculating the process of a and b coefficient. The calculating process of a and b coefficient in Schaeferâ€™s biology model was conducted through linear regression which has not yet been exact.Â  This isÂ  due toÂ  the model itself which is quadratic. Therefore to provide the solution is through quadratic process. The linear regression shows the value of fmsy and Ymsy 1.40 and 1.34 times smaller than quadratic process respectively. Based on the two graphs from the calculating process of a and b coefficient, it can be concluded that the utilization of yellowfin tuna fishery was still not optimal. According to the result based on the linear and quadratic regression, the maximum production of yellowfin tunaÂ  can be increased to 664,037 and 877,340 kg.Keywords: Population growth function, Schaeferâ€™s Biology Model, Utilization status, Yellowfin tunaABSTRAKDua jenis fungsi pertumbuhan populasi menjadi dasar pembentukan model biologi Schaefer, namun dalam kajian ini terdapat perbedaan dalam bentuk dan nilai r sebagai parameter biologi ditambah juga berdasarkan perbedaan metode perhitungan koefisien a dan b. Metode perhitungan koefisien a dan b model biologi Schaefer melalui regresi linear masih kurang tepat, karena model biologi Schaefer berbentuk kuadratik, sehingga penyelesaiannya harus melalui proses kuadratik. Nilai fmsy dan Ymsy dari proses regresi linear memiliki nilai 1,40 dan 1,34 kali lebih rendah dari proses kuadratik. Berdasarkan kedua kurva dari kedua metode perhitungan koefisien a dan b, maka status pemanfaatan perikanan tuna madidihang diduga masih belum optimal. Sehingga berdasarkan proses regresi linear dan kuadratik, maka produksi maksimal tuna madidihang masih dapat ditingkatkan sampai dengan 664.037 dan 877.340 kg.Kata kunci:Â  Fungsi pertumbuhan populasi, Model biologi Schaefer, Status pemanfaatan Tuna madidihang